UNDENSTANDING THE MEANING OF WHAT IS BEING AN ADULT - Ymiracy Nascimento de Souza Polak; Elis Rejane da Maia; Neide Martins; Simone Aparecida Lisniowski (Universidade Federal do Paraná, 1999)
It is a phenomenological study, which objectified to understand the meaning of what it is to be an adult for the population of the Second National Seminar on Adult Health held on August 19th to August 22nd, 1997. Forty -four (44) people were interviewed, ages ranging from 19 to 54 years. The analysis of their speeches enabled to distinguish five (5) major categories, which express the conception of adulthood for the interviewed group. Thus, being an adult means: to be responsible, to be financially and psychologically independent, to work, to be cidadany and to relate to others. The emerged categories reiterate Polak's conception of an adult (1997), which has guided the GEMSA (The Multiprofessional Study Group on Adult Health) studies.